1976
DOI: 10.1507/endocrj1954.23.485
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hypothalamic surgery on prolactin release induced by 5-hydroxytryptophan (5-HTP) in rats.

Abstract: SynopsisIntravenous injections of varying doses of 5-HTP (1, 3 and 5mg/100g body wt), a precursor of serotonin, caused a significant and dose-related increase in plasma prolactin concentrations in urethane-anesthetized rats. Increases in plasma prolactin concentrations caused by 5-HTP (1mg/100g body wt iv) were abolished by the concomitant administration of L-DOPA (2mg/100g body wt iv). Plasma prolactin levels were also significantly elevated following the injection of 5-HTP in rats with complete hypothalamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

1978
1978
1989
1989

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…Dennison et al [5] have reported similar increases in prolactin induced by chlorpromazine or metaclopromide in pituitary stalksectioned, estrogen-treated female monkeys. Our data are also consistent with the reports by Iwasaki et al [8] and Ohgo et al [13], who observed similar increases in prolactin in medial basal hypothalamic-lesioned rats following treat ment with the dopaminergic antagonists sulpiride and chlorpromazine.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Dennison et al [5] have reported similar increases in prolactin induced by chlorpromazine or metaclopromide in pituitary stalksectioned, estrogen-treated female monkeys. Our data are also consistent with the reports by Iwasaki et al [8] and Ohgo et al [13], who observed similar increases in prolactin in medial basal hypothalamic-lesioned rats following treat ment with the dopaminergic antagonists sulpiride and chlorpromazine.…”
Section: Discussionsupporting
confidence: 93%
“…This substance would be under inhibi tory dopaminergic control. The existence of a prolactin-re leasing factor in plasma has been demonstrated in lactating rats [3], 5-hydroxytryptophan-treated rats [13] and hyper prolactinemic women [6].…”
Section: Discussionmentioning
confidence: 99%
“…Lu and Meites [21] have reported that MES can block the prolactin releasing effect of serotonin in rats; this inhibition occurs in rats pretreated with fluoxetine, a drug that prevents serotonin reuptake [3], Moreover, prolactin release in response to suckling, a stimulus probably induced by serotonin [17,23], is blocked by MES pretreatment [II]. Some of the excitatory effects of serotonin on prolactin release are thought to occur within the MBH because an increase in prolactin secretion has been observed after 5-hydroxytryptophan administration in rats with an isolated MBH, but not in rats with MBH lesions [26]. Conversely, MacLeod [22] and Kridich el at.…”
Section: Discussionmentioning
confidence: 99%
“…Diluted rat plasma obtained 40 min after the injection of 5HT was capable of binding of 37% of 1 2 5~-~~~ addedin vitro Discussion. It is well known that 5HT stimulates the secretion of PRL by acting through the central nervous system (21)(22)(23). We have previously reported that hypothalamic VIP is involved, at least in part, in the secretion of PRL induced by 5HT in the rat, since 5HT stimulated VIP release from the hypothalamus (16,17)and immunoneutralization of endogenous VIP with anti-VIP serum blunted PRL release induced by 5HT in the rat (18)(19)(20).…”
Section: Nrsmentioning
confidence: 93%
“…The PSRS was specific for C-terminal residues of porcine PHI, showing no cross reactivity with porcine PHI(1-15), VIP, secretin, glucagon, TRH, human growth hormone releasing factor (GRF) and rat GRF (20). The extract of rat hypothalamus showed a parallel displacement of 1 2 5~-~~~( 1 -2 7 ) binding to the antiserum with porcine synthetic PHI(1-27) and PHI (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Analysis of variance and Student's ttest were used for statistical evaluat ion.…”
mentioning
confidence: 99%